Ecofriendly Biochar as a Low-Cost Solid Lubricating Filler for LDPE Sustainable Biocomposites: Thermal, Mechanical, and Tribological Characterization - Hany S. Abdo; Ibrahim A. Alnaser; Asiful H. Seikh; Jabair A. Mohammed; Sameh A. Ragab; Ahmed Fouly (International Journal of Polymer Science)
The potential of ecofriendly biochar, a carbon-rich byproduct of biomass pyrolysis, as a low-cost solid lubricating filler for low-density polyethylene (LDPE) sustainable biocomposites is investigated in this work. Tensile strength, hardness, thermogravimetric analysis (TGA), melting flow index (MFI), tensile test, flexural test, and frictional tests were used to characterize the biocomposites’ mechanical, thermal, and tribological properties. Energy-dispersive X-ray spectroscopy (EDS) was used to assess the chemical composition of the biochar, while field-emission scanning electron microscopy (FESEM) was used to capture the biochar morphology. The results showed that the incorporation of biochar in LDPE matrix increased the mechanical characteristics of the biocomposites and resulted in a significant increase in tensile strength, flexural strength, and hardness. More specifically, the LDPE+10 wt% composite outperformed the pure LDPE matrix by 1.9% in tensile strength and 47% in flexural strength. Furthermore, integrating biochar into LDPE composites enhances thermal stability, lowers the melt flow index (MFI), and boosts the hardness by 24.3% for the composite with 10% biochar content. Furthermore, biochar improves wear resistance and durability, with the LDPE10 composite exhibiting a friction coefficient that is 56.3% lower than pure LDPE. These findings indicate that biochar is a viable, cost-effective, and environmentally friendly filler for improving the performance of LDPE-based biocomposites for many varieties of applications.